Quad-Copter using ATmega328 microcontroller: article - Ismail, Mohamad Safari (UiTM, 2013)
This paper presents the design of Quad- Copter flying machine using Atmel microcontroller. The scope of this project involves both hardware design and software implementations. Potentiometer is used as an input device to produce analog signal. The analog signal is converted to digital form using Analog to Digital Converter (ADC) in Atmel microcontroller. The digital value is used by the microcontroller to generate Pulse Width Modulation (PWM) for the Electronic Speed Controller (ESC). ESC is a device that use with Brushless DC (BLDC) motor to control its speed. The project start with literature review where all the information for designing the control system of the quad rotor was gathered. All design requirements was obtained from the literature review. The requirements of the control system of four motor in quad rotor are microcontroller, Electronic Speed Controller (ESC), Brushless DC (BLDC) motors, propellers and the potentiometer as the throttle.